ENACT-ing Leadership at the State Level: A National Educational Network for Engaged Citizenship in State Legislatures - Glover, Robert; Cole, Kathleen; Owens, Katharine (Maine Policy Review, 2018)
The Educational Network for Active Civic Transformation (ENACT) is a nationwide network that serves as a hub for the pedagogical efforts of educators in 16 different states, with the ambitious goal of having an ENACT Faculty Fellow in all 50 states. However, ENACT courses go a step further engaging students directly in experiential learning exercises designed to affect policy change by working with policy advocacy groups, preparing policy briefs, engaging in strategic outreach and messaging, and meeting directly with policymakers in their state capitals to advocate for political change. In this paper, we argue that state politics represents a fruitful, yet often neglected, space for the development of political leadership skills. Accordingly, we will present ENACT as a pedagogical model for empowering students, enhancing their capacity for political leadership. Yet we also remain attuned to localized variation in the policy-making environment and state political culture.
Keywords: experiential learning; student engagement; state politics